Impacto da variação do espaço poroso do solo com ar no desenvolvimento de plantas de milho - Silva, Francisca Gleiciane da (2019)
The fraction of the volume of soil occupied with air is an essential part to guarantee the growth of the cultures. Assuming that less than 10% of aeration porosity is sufficient to guarantee the development of the plants, provided that other attributes of the pore space remain functional; and that the magnitude of this effect is dependent on soil density, the objective of this work was to evaluate the effects of different aeration porosities and soil density levels on the development of corn (Zea mays L.). The experiment was conducted in a greenhouse, in a randomized block design, in 2 x 5 factorial arrangement is composed of combinations of two bulk densities of soil (Ds): 1,6 e 1,7 g cm-³ and five aeration porosities (β): 7, 8, 9 10 e 12% with five replications. For each Ds, soil columns were made using a hydraulic press, and β as monitored by means of mercury tensiometers. Aeration porosity greater than 10% caused a reduction in most of the physiological variables, and for the range between 7 and 10%, the values were similar, mainly for photosynthesis and stomatal conductance. In the largest Ds the internal CO2 concentration was lower in the V5 stage, and in V12 there was an interaction between the factors. The stem diameter at all stages was lower at higher Ds, as well as at plant height at V12, which also decreased with increasing aeration porosity. In the VT stage, the physiological variables presented higher values in the plants under the highest Ds, however, the biomass production was lower, which reflected the concentration effect for some nutrients. The phosphorus content was influenced by the interaction between the factors and the magnesium only by the factor β. Root biomass production and root mass ratio increased in aeration porosity higher than 10%. It is concluded that the aeration porosity range between 7 and 10% does not cause a significant reduction in the values β of the analyzed variables, although the root production is smaller and can reduce the nutrient content of some nutrients. Aeration porosity greater than 10% allows a more favorable condition for soil air flow, however, plant growth is more limiting because it modifies attributes such as penetration resistance and soil water content. The increase in the level of Ds causes a reduction in most of the analyzed variables. The difference between the Ds treatments can be modified with phenological stages as an adaptive response to the condition considered more limiting.